An Insight To Translation Strategies Of â€œTidak Ada New York Hari Iniâ€ Poems (EUFONI: Journal of Language, Literary, and Cultural Studies, 2018)
ABSTRACT This paper examines several translation strategies in attempting to meet naturalness Tidak Ada New York Hari Ini poems. Recently, there have been wide interests to investigate how translators work on literary translation and anticipate the cultural distance between the source text and the target text. According to Nida (2004), there is no absolute correspondence between two languages. In addition she proposes that the translators also need to pay attention to the figurative expressions and metaphors in literary translation. The data collection and analysis were done by reading the poems closely in which the target text and the source text were compared in terms of equivalence. The writer also interviewed the translator of the poetry, John H. McGlynn. Keywords: Translation methods, Newmark, Semantics translation, Poems